Pequenos mamíferos terrestres do cerrado (Rodentia: Didelphimorphia): seleção de habitats, áreas de vida e padrões direcionais de deslocamento - Carmignotto, Ana Paula (1999)
The influence of flooding in a community of small mammals from the Central Brazilian Cerrado, state of Goiás, was studied in an area of 2,0 ha near the hydroelectric dam of Serra da Mesa. The community studied showed a high value of species richness when compared to other areas of Cerrado and rainforest sites. The relative abundance of species, on the other hand, indicated that rarity is a very important feature of this community. The species showed great fidelity to their habitats, even though the effect of flooding diminished their preferred areas. Most individuals haven't changed their home range or the mean distance moved between successive captures throughout the study, suggesting virtually no dispersal. The analysis of the movements of individuals and populations didn't show any preference of direction. The synchronous results obtained in relation to the drastic reduction of the parameters analyzed (capture success, species richness, abundance and population density) revealed that the flooding was responsible to a great extent for such reductions, leading to the extinction of the small mammals in the study area.